Penentuan Kedalaman dan Ketebalan Akuifer Menggunakan Metode Seismik Bias (Studi Kasus Endapan Alluvial Daerah Sioux Park, Rapid Creek, South Dakota, United State of America) - Listiyani, Fenti; Nurwidyanto, M. Irham; Yulianto, Gatot (BERKALA FISIKA, 2006)
Data processing of refraction Seismic has been done by using the secondary data in area of Sioux Park, Rapid Creek, South Dakota, United State of America with the trajectory of seismic SP#1 which  has geology structure of alluvial sediment. The sediment Alluvial has a form of water carrier rock precipitated by Rapid Creek Tthe data processing of refraction Seismic usedin this experiment is  Reciprocal Hawkins methode that  represent a method that develop concept of time depth recognition. The time Depth from the refractor is  equal for the travel of critical time from the aspect of between refractor and surface less than time required for the ray path of projection of area refractor at a speed of refractor. Results   of  the seismic refracted obtained: first layer consist of clay  functioning as covering laye, the second layer lapped over from clay, sand, and gravel functioning as carrier coat irrigate or coat acquife and the   third layer lapped over from stone napal, functioning as waterproof coat ( impermeable). Deepness of layer acquifer vary from 0.93 ft - 12.01 ft ( 0.28 m – 3.66 m), and their thickness vary from 0.86 ft – 14.43 ft ( 0.26 m – 4.40 m). The geometry of these  acquiferare in the form of free acquifer  or unconfined aquifer. Keywords: seismic refraction, ground water